Personal branding of new political parties in Indonesia: PSI, Perindo, and Gelora - Reksi Anggara; Ahmad Palemba; Achmad Nurmandi; Misran; Mohammad Jafar Loilatu (Jurnal Studi Komunikasi, 2024)
In this digital era, social media has become a very effective tool for candidates and political parties to communicate, influence voters, and promote their messages. The tight world of politics requires political parties to create personal branding that differentiates them from other political parties. This research aims to explore in-depth the strategies for building personal branding carried out by new Indonesian political parties on social media. The researcher focused on three new political parties active on social media, namely the Indonesian Solidarity Party (PSI), the Indonesian Unity Party (Perindo), and the Indonesian People's Wave Party (Gelora). This research analyses the official Twitter accounts of the three parties from September 2020 to June 2023. The choice of this period is essential to maintaining data consistency and ensuring that the analysis can find strategies for building personal branding without interference from intense campaign activities. This research uses qualitative methods with a Qualitative Content Analysis (QCA) approach. NVivo12 plus software was used to help visualise the data. This research shows that PSI is building its personal branding using a millennial-style approach, Perindo is focusing on welfare issues, and Gelora Party is relying on experienced senior figures. Overall, this research emphasises that an effective personal branding strategy requires a deep understanding of the target audience, selecting relevant issues, and using credible figures.